Mensitieri, G. (ed.) (2020) The most beautiful job in the world, London, Bloomsbury, p. 271. - Abdel Qader, Sumaya (Cuadernos de Relaciones Laborales, 2024)
The article introduces Giulia Mensitieri’s book, "The Most Beautiful Job in the World," which sheds light on the gap between the glamorous image of the fashion industry and the harsh realities faced by those working within it. The book focuses on luxury fashion and explores the exploitative practices, inequalities, and emotional toll experienced by stylists, photographers, and designers. It emphasizes the paradoxical nature of the industry, combining prestige with precariousness and self-fulfillment with self-exploitation. The concepts of capitalism, dreams, oxymorons, and heterotopia are analyzed to better understand the complexities of the fashion industry.